A Rising Endemic within a Pandemic: Impact of Inflation on Mental Health - Larik, Muhammad Omar; Zoha Khan; Maryam Urooj (Journal of the Pakistan Medical Association, 2023)
Madam, Inflation describes the increment in the cost of living over a certain period, occurring in light of extreme events that impact the economy. The current wave of inflation results from the coalition of events mainly stemming from the COVID-19 pandemic, producing a myriad of economic disruptions. Rising food insecurity, hikes in electricity prices, and fuel costs leave families facing an unprecedented financial crisis. Moreover, the turmoil created by the recent flooding due to record-breaking rainfall affecting Sindh, Balochistan, and Khyber Pakhtunkhwa has fuelled the current inflation wave in Pakistan. The impact of such issues can be devastating in multiple respects. The convulsion of the economy has given rise to mental health disorders nationwide, resulting in a decline in physical health. Those suffering from mental illnesses are more likely to suffer from chronic physical conditions, including Alzheimer’s disease, diabetes mellitus, thyroid disorders, and more1. A survey conducted by the American Psychological Association (APA) illustrated that 9 in 10 individuals perceive financial hardships as a major source of stress – notably greater than the perception during the pre-pandemic era2. Furthermore, it is common for stressed individuals to resort to unhealthy coping mechanisms, such as smoking3 – increasing the risk of pulmonary diseases and cancers, providing the evident association between mental and physical health. This shows the undeniable impact of the pandemic on financial constraints across the world. Pakistan’s overall disregard for mental health has recently been corroborated. The World Health Organization (WHO) introduced the “Comprehensive Mental Health Action Plan 2013-2020” to improve mental health globally. However, as per WHO’s “World Mental Health Report” analysis, most countries, including Pakistan, did not adhere to the plan, highlighting the lack of consideration towards mental health4. Moreover, Pakistan lacks sufficient resources to handle an endemic wave of mental disorders. Having one of the lowest psychiatrist-to-patient ratios worldwide – with only 500 psychiatrists serving a colossal population of 220 million. These statistics substantiate the urgency to emphasize the indispensability of psychiatry as a career opportunity5. Local authorities must invest in effective relief programs, especially for the impoverished disproportionately affected by the economic crisis. As a nation, it is paramount to possess readiness for intervention at times of psychological distress, and if left rampant, may enter a vicious cycle of deteriorating mental health, precipitating to deteriorating physical health, further crippling the economy.